Evaluating the effects of chlorhexidine and vitamin c mouthwash on oral health in non-surgical periodontal therapy: a randomized controlled clinical trial - Nurdan Ozmeric; Ayaz Enver; Sila Cagri Isler; Ceren Gökmenoğlu; Merve Topaloğlu; Hilal Selamet; Gökçen Altun; Selin Aykol Sayar (Scientific Reports)
Abstract Chlorhexidine (CHX) is the most commonly used mouthwash with proven antiplaque and antibacterial activity. The aim is to evaluate the effect of vitamin C (VitC) in CHX mouthwash on plaque accumulation and gingivitis, and to compare it with CHX alone mouthwash and antiseptic phenol-containing mouthwashes. This study conducted as a multicenter, randomized, controlled, double-blind, parallel design clinical study. Sixty patients were included, randomly divided into three groups. 1. Antiseptic phenol agent (P, Phenol), 2. Antiseptic bisbiguanide agent CHX-only (CHX) and 3. Antiseptic bisbiguanide agent CHX + VitC mouthwash (CHX + VitC). The study assessed oral hygiene and periodontal health status, followed by scaling and root planning (SRP) and subsequent polishing. After using the mouthwash for 60 s twice daily along 14 days, patients recalled for evaluation of plaque index (PI), gingival index (GI), bleeding on probing (BOP) and staining. One-way analysis of variance (ANOVA) was used to compare the differences formed between groups and Tukey multiple comparison analysis was used to determine groups that showed the differences. Statistical significance was determined using a p-value threshold of 0.05. There were no significant differences between the groups regarding baseline PI, GI and BOP (p > 0.05). Changes at 14th day in PI, GI and BOP in all groups were similar and no significant differences were observed (p > 0.05). Regarding ‘all surfaces’, staining density of two mouthwashes containing CHX was significantly higher than that of P mouthwash. CHX, CHX + VitC, and P mouthwashes appeared to exhibit comparable effects as oral hygiene adjuncts to periodontal mechanical treatment, with the exception of staining, which was more noticeable in the CHX groups compared to the P group. Adding vitamin C did not enhance the effects of CHx alone.